Akute myeloische Leukämie bei Erwachsenen - Spiekermann, Karsten; Shen, Anne-Sophie (DMW - Deutsche Medizinische Wochenschrift, 2018)
There are several changes in the revised WHO classification for acute leukemia. The latest version of the European Leukemia Network (ELN)-risk classification defines AML with mutations in RUNX1, ASXL1 or TP53 to fall in the unfavorable risk group. Consequently, the somatic molecular genetic testing at the time of initial diagnosis should encompass these before mentioned three genes next to the already routine testing of NPM1, CEBPA and FLT3-ITD. Several new innovative substances have been developed and approved for AML therapy. The multikinase inhibitor midostaurin is a new substance in the induction therapy for patients with FLT-3 mutated AML. CPX-351 (cytarabin and daunorubicin in liposomatic formulation in a defined molar relation) is a new option for therapy associated AML and AML with myelodysplastic changes. Enasidenib is a targeting drug for relapsed or refractory AML with IDH2 mutation. Gemtuzumab, a CD33 + antibody-drug-conjugate is approved for CD33 positive cases.
Keywords: AML; zielgerichtete Therapie; Risikoklassifikation